Development of Potato-Derived Carbon Nanofibers as Sustainable Moisture-Regulating Supporting Layers for Photovoltaic Modules - Indri Dayana; Habib Satria; Nidya Chitraningrum; Mega Puspita Sari; Tino Hermanto; Yopan Rahmad Aldori; Dadan Ramdan; Syofyan Anwar Syahputra; Dina Maizana; Moranain Mungkin; Junaidi Junaidi; Ade Irma Sagala; Siti Utari Rahayu (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
Moisture-induced degradation remains a critical reliability issue in photovoltaic (PV) modules, particularly in humid tropical climates. While biomass-derived carbon materials have been widely investigated for electrochemical applications, their use as functional supporting layers in PV modules remains limited. This study develops potato-derived carbon nanofibers through moderate-temperature carbonization (700 °C, N₂ atmosphere) followed by electrospinning. Structural and chemical properties were evaluated using XRD, FTIR, Raman spectroscopy, and BET surface area analysis. Morphology and fiber diameter distribution were examined via SEM. Electrical conductivity was measured using a four-point probe method. Water vapor permeability (WVP) and biodegradation behavior were assessed to evaluate durability and moisture regulation capability. The synthesized material exhibits predominantly amorphous turbostratic carbon with characteristic D and G Raman bands (ID/IG ≈ 0.92), specific surface area of 186 ± 12 m²/g, and electrical conductivity of 3.8 ± 0.4 S/m. Nanofiber diameters range from 72–108 nm (mean ± SD). Controlled WVP (3200–4100 mg/day/L) and moderate biodegradability (8–12% mass loss over 14 days) indicate balanced vapor diffusion and structural integrity. The results demonstrate the feasibility of potato-derived carbon nanofibers as sustainable moisture-regulating supporting layers in photovoltaic modules.